Pengembangan Media Pembelajaran Berbasis Video dalam Meningkatkan Pemahaman Qur'an dan Makna (Qurma) pada Surat Al-Humazah di MI Narrative Quran Lamongan - Munawaroh, Siti; Hamid, Abdulloh; Hana, Rudy Al; Salehudin, Mohammad (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
The Qur'an as a guide to life must be understood its meaning. Often found, the study of short Surats material revolves around reading verses, memorizing, and knowing the meaning only. In MI Narrative Quran, there are subjects of Qur'an and Meaning (Quran dan Makna/Qurma). In addition to being able to read and know its meaning, students are also required to be able to understand the content of the Qur'an. The research aims to create a video-based learning media product in understanding Qurma Surat Al-Humazah. This research using Research and Development (R&D) method by applying six steps, namely: potential and problems, data collection, product design, design validation, design revision, and product trial. The feasibility of learning media in the form of video has been assessed using questionnaires by media experts, material experts, and grade 3 students. Research data in the form of quantitative data is then analyzed using descriptive quantitative analysis techniques. The study results were video-based learningi mediai productsi in thei formi of mp4i files equipped with music background, animation, and narrator. Video feasibility obtained a percentage of 96.06% from media experts, and material experts obtained a percentage of 90.41% with excellent classification. From prospective users (grade 3 students) obtained a percentage of 96.66% with the classification strongly agree in using it. That way, the video-based learning media is worth using in the learning process.